2016
DOI: 10.1111/tmi.12755
|View full text |Cite
|
Sign up to set email alerts
|

Actual and predicted prevalence of alcohol consumption during pregnancy in the WHO African Region

Abstract: Abstractobjective To estimate the prevalence of alcohol consumption and binge drinking during pregnancy among the general population in the World Health Organization (WHO) African Region, by country.methods First, a comprehensive systematic literature search was performed to identify all published and unpublished studies. Then, several meta-analyses, assuming a random-effects model, were conducted to estimate the prevalence of alcohol consumption and binge drinking during pregnancy among the general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 51 publications
8
50
2
Order By: Relevance
“…(Martinez et al, 2011; WHO, 2014b; Popova et al, 2016a). Its cost is low compared to commercially-made alcoholic beverages in many parts of Africa (Mccall, 1996; Willis, 2002) and quantifying its amount is challenging because home brews are often consumed in containers of various sizes (Hahn et al, 2012; Thakarar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Martinez et al, 2011; WHO, 2014b; Popova et al, 2016a). Its cost is low compared to commercially-made alcoholic beverages in many parts of Africa (Mccall, 1996; Willis, 2002) and quantifying its amount is challenging because home brews are often consumed in containers of various sizes (Hahn et al, 2012; Thakarar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Burkina Faso is a country in Africa where the use of alcohol is increasing among women; it has among the highest national proportion of women consuming alcohol in the continent, 30% (Martinez et al, 2011). In 2016, a systematic review highlighted that the predicted prevalence of any amount of alcohol consumption during pregnancy among the general population in Burkina Faso was 11.3% (Popova et al, 2016a). According to the WHO, the level of total alcohol consumption was 6.8 litres of pure alcohol per capita for adults above 15 years of age from 2008 to 2010 (WHO, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…1). The current study was conducted by compiling studies done in different east African countries; Ethiopia (10, 11, 17, 19-22, 32, 33), Uganda (7,16), Tanzania (12,14,15), and Kenya (13,18). Fifteen cross-sectional studies and two case-control and one cohort study articles were used for the final analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…The prevalence of alcohol use (any amount) during pregnancy found to be higher in Africa countries including East Africa. From a compilation of the studies identified in Africa, the prevalence of alcohol use during pregnancy ranges from 2.5% to 37.9% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Different determinant factors are identified for maternal alcohol drinking and use disorder during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation